LINC00467 promotes cell proliferation and metastasis by binding with IGF2BP3 to enhance the mRNA stability of TRAF5 in hepatocellular carcinoma. (20th January 2020) - Jiang, Wenjin; Cheng, Xueling; Wang, Tao; Song, Xuepeng; Zheng, Yanbo; Wang, Ligang
Abstract: Background: Hepatocellular carcinoma (HCC) has been recognized as a member of the most common human malignant tumors globally. According to multiple studies, long noncoding RNAs (lncRNAs) have been defined as vital regulators in tumor progression. Although previous studies have indicated that lncRNA long intergenic non‐protein coding RNA 467 (LINC00467) exerts oncogenic effect in tumorigenesis and the development of cancers, the specific function that LINC00467 induces in HCC remains obscure. Methods: LINC00467 expression was examined by a quantitative reverse transcriptase‐polymerase chain reaction. CCK‐8, EdU, transwell, western blotting and caspase‐3 activity analyses were utilized to testify the role of LINC00467 in HCC. The interaction between IGF2BP3 and LINC00467 (or TRAF5) was investigated by luciferase reporter, RIP and RNA pull‐down assays. Results: LINC00467 upregulation in HCC tissues and cells was observed. LINC00467 silencing suppressed cell proliferation and metastasis, whereas it facilitated cell apoptosis in HCC. The gene for tumor necrosis factor receptor‐associated factor 5 (TRAF5) was a neighboring gene of that for LINC00467 and its expression was positively modulated by LINC00467 in HCC. TRAF5 knockdown inhibited HCC progression. LINC00467 deficiency could decrease the mRNA stability of TRAF5 in HCC. Insulin‐like growth factor‐2 messenger RNA‐binding protein 3 (IGF2BP3) could bind with LINC00467 and its depletion could lower TRAF5 mRNA stability in HCC. Final rescue assays further indicated that downregulation of IGF2BP3 or TRAF5 acted against LINC00467 upregulation‐mediated function on HCC progression. Conclusions: LINC00467 promotes cell proliferation and metastasis by binding with IGF2BP3 to enhance the mRNA stability of TRAF5 in HCC.